A benign entity – cerebral multinodular and vacuolating neuronal tumor - Kış, Naciye; Erok, Berrin; Kılıç, Harun; Önder, Hakan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. Multinodular and vacuolating neuronal tumor (MVNT) of the cerebrum is a rare benign, mixed glial/ neuronal lesion which has been included in the recent (2016) World Health Organization (WHO) Classification of the central nervous system tumors.Most of the reported cases are remarkable with adult onset seizure in the literature.They can also be found incidentally in nonepilepsy patients with or without headache We aimed to present this unique entity with its typical magnetic resonance imaging (MRI) features. Description of the case. A 21-year old man presented with complaint of headache that increased in frequency within the last few months.No relevant seizure or any other signs of note.He was diagnosed with MVNT by imaging andstarted to be followed- up.The repeat MRI 6 months later showed no interval changes. Conclusion. Clinicians should be aware of that it is a do not touch lesion in asymptomatic patients with no need for biopsy or surgery and follow up imaging is sufficient when presented with the typical MRI manifestations. Surgical resection may be required for seizure control and was reported in few cases with no tumoral regrowth in the literature.
Keywords: do not touch brain tumors; magnetic resonance imaging; multinodular and vacuolating neuronal tumor